Increasing age and experience: are both protective against motorcycle injury? A case-control study. Issue 1 (1st March 2000) - Mullin, Bernadette; Jackson, Rodney; Langley, John; Norton, Robyn
Abstract : Objectives —To assess the associations between age, experience, and motorcycle injury. Setting —Motorcycle riding on non-residential roads between 6 am and midnight over a three year period from February 1993 in Auckland, New Zealand. Methods —A population based case-control study was conducted. Cases were 490 motorcycle drivers involved in a crash and controls were 1518 drivers identified at random roadside surveys. Crash involvement was defined in terms of a motorcycle crash resulting in either a driver or pillion passenger being killed, hospitalised, or presenting to a public hospital emergency department with an injury severity score ≥5. Results —There was a strong and consistent relationship between increasing driver age and decreasing risk of moderate to fatal injury. In multivariate analyses, drivers older than 25 years had more than 50% lower risk than those aged from 15–19 years (odds ratio (OR) 0.46; 95% confidence interval (CI) 0.26 to 0.81). In univariate analyses, a protective effect from riding more than five years compared with less than two years was observed. However, this protection was not sustained when driver age and other potential confounding variables were included in the analyses. Familiarity with the specific motorcycle was the only experience measure associated with a strong protective effect (OR (≥10 000 km experience) 0.52; 95% CI 0.35 to 0.79) in multivariate analyses. Conclusions —Current licensing regulations should continue to emphasise the importance of increased age and might consider restrictions that favour experience with a specific motorcycle.